xyz

Level 1

I f x + y + z = 0 t h e n w h a t i s t h e v a l u e o f 1 x 2 + y 2 z 2 + 1 y 2 + z 2 x 2 + 1 z 2 + x 2 y 2 ? If\quad x+y+z=0\quad then\quad what\quad is\quad the\quad value\quad of\\ \frac { 1 }{ { x }^{ 2 }+{ y }^{ 2 }-{ z }^{ 2 } } +\frac { 1 }{ { y }^{ 2 }+{ z }^{ 2 }-{ x }^{ 2 } } +\frac { 1 }{ { z }^{ 2 }+{ x }^{ 2 }-{ y }^{ 2 } } ?


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ronak Agarwal
Aug 22, 2014

S = 1 x 2 + y 2 z 2 + 1 y 2 + z 2 x 2 + 1 z 2 + x 2 y 2 S=\frac { 1 }{ { x }^{ 2 }+{ y }^{ 2 }-{ z }^{ 2 } } +\frac { 1 }{ { y }^{ 2 }+{ z }^{ 2 }-{ x }^{ 2 } } +\frac { 1 }{ { z }^{ 2 }+{ x }^{ 2 }-{ y }^{ 2 } }

In first term use z = x y z=-x-y , in second term use x = y z x=-y-z , in third term use y = x z y=-x-z to get :

S = 1 2 x y + 1 2 y z + 1 2 z x S=\frac { 1 }{ -2xy } +\frac { 1 }{ -2yz } +\frac { 1 }{ -2zx }

S = 1 2 ( x + y + z x y z ) \Rightarrow S=\frac { -1 }{ 2 } (\frac { x+y+z }{ xyz } )

Now since x + y + z = 0 x+y+z=0 we have :

S = 0 \boxed{S=0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...